Pengetahuan Komuniti Dalam Peningkatan Kedayatahanan Menghadapi Banjir Di Alor Setar, Kedah - Zainal Abidin, Izza Shafini (2016)
Community preparedness for disaster caused by climate change is a key agenda for achieving sustainable cities and communities. It is undeniable that communities should be prepared to face any risk and vulnerabilities posed by unexpected disasters. This study aims to explore the knowledge and skills of communities in reducing the risk of flood. Besides, this study also aims to look at the relationship between factors that influence the knowledge and skills of communities in flood risk reduction. Moreover, this study also aims to identify the potential and challenges of stakeholders including government agencies, representatives of community-based organisations (cbos) and representatives of non-governmental organisations (ngos) to improve the knowledge and skills of local communities in order to reduce the flood risk. This study used random sampling through the questionnaire survey involving 100 respondents and purposive sampling involving five representatives of stakeholders. The study found that the experience did influence community behaviour change and may potentially increase the adaptation to the future disaster.